Transcription termination at the tryptophan operon attenuator is decreased in vitro by an oligomer complementary to a segment of the leader transcript. - Winkler, M E (1982)
A DNA oligomer 15 nucleotides long was used to probe the involvement of RNA secondary structure in the control of transcription termination at the attenuator of the tryptophan (trp) operon of Escherichia coli. This 15-mer is perfectly complementary to a segment of trp RNA that is thought to play a role in regulation of attenuation. When added to an in vitro transcription reaction mixture containing wild-type E. coli or Salmonella typhimurium trp operon templates, the complementary 15-mer caused a 4-fold increase in read-through transcription. By contrast, the 15-mer did not affect attenuation when a mutant E. coli template was used that does not allow formation of a crucial RNA secondary structure. Control experiments established that oligomers that were not complementary to E. coli trp leader RNA did not affect attenuation and that the 15-mer did not reduce termination when the transcript lacked a complementary region. Other experiments established that the 15-mer did not increase read-through transcription by allowing RNA polymerase molecules that might have already stopped at the attenuator to resume transcription. These findings provide direct support for the view that alternate base-paired structures control transcription termination at the trp attenuator.